A Study of the Optimal Allocation of Shunt Capacitor Based on Modified Loss Sensitivity Algorithm - Warid, Warid Sayel; Mohsin, Emad Allawi (Iraqi Journal for Electrical and Electronic Engineering, 2010)
Minimization of active power losses is one of the essential aims for any electric utility, due to its importance in improvement of system properties towards minimum production cost and to support increase load requirement. In this paper we have studied the possibility of reducing the value of real power losses for (IEEE-14- Bus bar) global system transmission lines by choosing the best location to install shunt capacitor depending on new algorithm for calculate the optimal allocation, which considering the value of real power losses derivative with injection reactive power as an indicator of the ability of reducing losses at load buses. The results show the validity of this method for application in electric power transmission lines.